1995
DOI: 10.1002/ijc.2910630203
|View full text |Cite
|
Sign up to set email alerts
|

Is the apparent rise in cancer mortality in the elderly real? analysis of changes in certification and coding of cause of death in England and Wales, 1970–1990

Abstract: The effect of changes in recording and coding of cause of death on trends in cancer mortality in England and Wales in persons aged 45 and over during 1970-1990 is reviewed. During this period, all-cancer mortality rates increased only at ages over 75 in males and over 55 in females. Rises in cancer mortality were largely due to increases in cancer of lung, prostate and unspecified site in men, and of lung, breast and unspecified site in women. Death coding and certification artefacts were much larger in older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…7,14,15 However, previous studies have indicated several sources of potential error, particularly in assigning the cause of death in elderly prostate cancer patients with considerable comorbidity. 5,10,[16][17][18] In fact, more than half of the deaths in patients with prostate cancer are due to causes other than prostate cancer. 19 In England and Wales, nearly a half of the noted increase in prostate cancer mortality from 1970 to 1990 for men 75-84 years old was accounted for by inaccuracies in death certification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,14,15 However, previous studies have indicated several sources of potential error, particularly in assigning the cause of death in elderly prostate cancer patients with considerable comorbidity. 5,10,[16][17][18] In fact, more than half of the deaths in patients with prostate cancer are due to causes other than prostate cancer. 19 In England and Wales, nearly a half of the noted increase in prostate cancer mortality from 1970 to 1990 for men 75-84 years old was accounted for by inaccuracies in death certification.…”
Section: Discussionmentioning
confidence: 99%
“…19 In England and Wales, nearly a half of the noted increase in prostate cancer mortality from 1970 to 1990 for men 75-84 years old was accounted for by inaccuracies in death certification. 17 Trends in prostate cancer mortality have also been shown to follow the rise and fall of newly detected cases, suggesting misattribution of the cause of death among prostate cancer patients. 20 However, little information is available for death-cause attribution in this era of the widespread use of PSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not a site where the mortality data are likely to have been affected appreciably by changes in diagnostic technology or criteria. Breast cancer mortality data at older ages are particularly susceptible to artefacts of death certification and of coding selection of underlying cause of death (Grulich et al, 1995), but again this does not appear likely to explain most of the increase. Screening in recent years may have resulted in the detection of incident cases that would not otherwise have been known, or that would have been diagnosed later, but it is unlikely to have increased apparent mortality, and indeed in the long term should lead to a decrease in mortality.…”
mentioning
confidence: 99%
“…It should also be noted that data on trends at middle and younger ages are likely to be more reliable than those for older ages (Grulich et al, 1995), although the high rates of cancer at older ages make these important to consider too from a public health and health care perspective.…”
mentioning
confidence: 99%